Forest structure along a 600 km transect of natural disturbances and seasonality gradients in central‐southern Amazonia. (31st May 2016) - Schietti, Juliana; Martins, Demétrius; Emilio, Thaise; Souza, Priscila F.; Levis, Carolina; Baccaro, Fabricio B.; Pinto, José Luiz Purri da Veiga; Moulatlet, Gabriel M.; Stark, Scott C.; Sarmento, Kelly; de Araújo, R. Nazaré O.; Costa, Flávia R. C.; et al.
Summary: A negative relationship between stand biomass and the density of stems is expected to develop during the self‐thinning process in resource‐limited forests; this leads to a large proportion of the total biomass occurring in large trees. Nevertheless, frequent disturbance regimes can reduce self‐thinning and the accumulation of large trees. We investigated size–density relationships and the contribution of large trees (dbh ≥ 70 cm) to stand biomass in 55 1‐ha plots along a 600 km transect in central‐southern Amazonia. The effects of natural‐disturbance gradients (frequency of storms and soil characteristics) and seasonality on forest‐structure components (density of stems and mean individual mass) and stand biomass were examined. Contrary to self‐thinning predictions, stand biomass increased in forests with higher stem densities. Large trees contained only an average of 5% of stand biomass, and half of the stand biomass was represented by small trees with diameters < 27 cm. These findings indicate that persistent or strong disturbance plays a critical role in forest structure and biomass in the central‐southern Amazon. Frequent storms were identified as an important source of disturbance in the region. Forests under higher frequency of storms had trees with lower individual mass and higher stem packing. More physically restrictive soils seem to magnify the effects of exogenous disturbances limiting individual tree size. Forests in areas with longer dry seasons had lower stem densities; however, individual mass was higher in these areas. These structural components of biomass seem to counterbalance each other in generating total stand biomass. Seasonality affected forest structural components but not stand biomass. Synthesis . Forests of central‐southern Amazonia are not resource limited and accumulate most part of their biomass in small‐ to mid‐sized trees. The effects of environmental gradients on specific structural components of stand biomass differ such that strong positive effects on one component can mitigate strong negative effects on other component. Future work on the determinants of stand biomass should investigate forest structure and the contributions of individual components to stand biomass. Abstract : Forests of central‐southern Amazonia are not resource limited and accumulate most part of their biomass in small‐ to mid‐sized trees. Disturbance gradients given by the frequency of storms and soil conditions and seasonality were investigated as possible underlying factors influencing this pattern and the variations in stem density, mean individual mass and ultimately above‐ground woody biomass in these forests.